The Omni-buss !!! - Heath, William, 1795-1840 (McLean, Thomas, 1829)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Carriages & coaches; Omnibus; Great Britain -- Politics and government -- 1800-1837; Catholic emancipation